SPELLING OF WORDS WITH THE LETTER COMBINATION OU AND THE FORMS –ILLE, – EILLE - Nargiza Narmatovna Nuritdinova (Western European Studies, 2025)
This article provides a scientific analysis of the spelling features of the ou letter combination as well as units ending in –ille and –eille found in loanwords used in the Uzbek language. The study is based on the current Uzbek spelling rules, explanatory dictionaries, and written language materials. The results show that the spelling of these words mainly relies on adaptation to pronunciation and the phonetic laws of the Uzbek language. The article has practical significance in improving students’ literacy and strengthening spelling norms
Keywords: spelling; ou letter combination; ille and –eille forms